Antimicrobial Susceptibility, and Molecular Characterization of Staphylococcus aureus Isolated From Different Raw Milk Samples in China - Huimin Liu; Huimin Liu; Lei Dong; Lei Dong; Yankun Zhao; Lu Meng; Lu Meng; Jiaqi Wang; Jiaqi Wang; Cheng Wang; Nan Zheng; Nan Zheng (Frontiers in Microbiology, 2022)
Staphylococcus aureus (S. aureus) is one of the main pathogens in different raw milk and dairy products, which may lead to economic losses. Staphylococcus aureus is a significant and costly public health concern because it may enter the human food chain and contaminate milk causing foodborne illness. This study aimed to investigate the prevalence, antimicrobial susceptibility and virulence genes of S. aureus in raw milks. In total, 125 raw milk samples collected from goat (n = 50), buffalo (n = 25), camel (n = 25), and yak (n = 25) were collected from 5 provinces in China in 2016. Out of 125 samples, 36 (28.8%) S. aureus were isolated (16 from goat, 9 from buffalo, 6 from camel, and 5 from yak). Out of 36 S. aureus, 26 strains (26/36, 72.2%) showed antibiotics resistance, and 6 strains isolated from goats were identified as methicillin-resistant S. aureus (MRSA). The antimicrobial resistance against Penicillin G, tetracycline and gentamicin was 50% (18/36), 41.7% (15/36), and 36.1% (13/36), respectively. 19 S. aureus (52.8%) were considered as multidrug resistant. The highest prevalence of resistant S. aureus was observed in goat milk (13/36, 36.1%). Among the 36 strains, 16 isolates harbored three or more resistant genes. The resistance genes were detected in 25 S. aureus, including 13 strains in goat, 5 strains in buffalo, 4 strains in camel, and 3 strains in yak. Among the 26 resistant strains, 61.5% of isolates harbored three or more resistant genes. The resistance genes were detected in 25 S. aureus, including 13 strains in goat milk, 5 strains in buffalo milk, 4 strains in camel milk, and 3 strains in yak milk. The most predominant resistance genes were blaZ (18/26, 69.2%), aac6′-aph2″ (13/26, 50.0%), and tet(M) (10/26, 38.5%). The mecA, ant(6)-Ia and fexA gene were only detected in S. aureus from goat milk. The most predominant toxin gene were sec (8/26, 30.8%). The majority of S. aureus were multidrug resistant and carried multiple virulence genes, which may pose potential risk to public health. Our findings indicated that the prevalence and antimicrobial resistance of S. aureus was a serious concern in different raw milks in China, especially goat milks.